Estudo das condições de trabalho em Unidade Básica de Saúde no município de São Carlos: a perspectiva dos diferentes atores. - Silva, Nilson Rogério da (Universidade Federal de São Carlos, 2003)
The demand for public health services has increased gradually in the last few years due to the high rates of increasing unemployment, high cost of private health plans and the transference of health actions from the federal and state sphere to the local one. In this way, the public local health system has found difficulties to comply with the users demands, since this is higher than the offered services. This research is aimed at the studies of the activities carried on at one Health Basic Unit (UBS) of São Carlos City, trying to identify the relationship between the working conditions and the workers health, aiming the replanning work. For this study, 33 (thirty three) employees from the UBS were considered (doctors, nurses, nurse assistants, dentists, dentist assistants, administrative assistants). The work conclusion is that the working of the unit is permeated by different situations that cause embarrassment to the unit staff and users, among them we can mention: a) the unit is working routine is concentrated during the morning hours, facilitating work overloading and conflicts; b) lack of criteria for the right dimensioning of the unit is staff; c) fragile structure to deal with the absenteeism generating extra working hours and double period of work; d) communication process truncated between supervisors and employees; e) obsolete equipment that make difficult the execution of activities, because demand extra effort (physical and mental) from the employee f) lack of policy for the acquisition, substitution and update of equipment; g) lack of planning for the unit layout, where there is no consideration for the best distribution of rooms, interrelationship between the executed procedures, in the flow of services being offered, minimum space for the execution of tasks, equipment and furniture and waiting rooms; need of training and qualification to deal with the public, professional update, information to avoid contamination with material and diseases. The work in the UBS reveals suffering situations with the presence of: planning the work without the worker is participation, information flow truncated complaints as to the professional recognition. Pleasurable situations refer to the user satisfaction with the possibility to reduce the suffering of the other, of the human care practice.
Keywords: Estudo do trabalho; Ergonomia; Saúde do trabalhador; Unidade Básica de Saúde; Ergonomics; Worker health; Health basic unit; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA